New Insights on the Evolution of the Sweet Taste Receptor of Primates Adapted to Harsh Environments - Nur Aida, Md Tamrin; Ramlah, Zainudin; Yuzine, Esa; Halimah, Alias; Mohd Noor, Mat Isa; Croft, Laurence; Mohd Tajuddin, Abdullah (MDPI, 2020)
Taste perception is an essential function that provides valuable dietary and sensoryinformation, which is crucial for the survival of animals. Studies into the evolution of the sweet tastereceptor gene (TAS1R2) are scarce, especially for Bornean endemic primates such asNasalis larvatus(proboscis monkey),Pongo pygmaeus(Bornean orangutan), andHylobates muelleri(Muller’s Borneangibbon). Primates are the perfect taxa to study as they are diverse dietary feeders, comprising specialistfolivores, frugivores, gummivores, herbivores, and omnivores. We constructed phylogenetic trees oftheTAS1R2gene for 20 species of anthropoid primates using four different methods (neighbor-joining,maximum parsimony, maximum-likelihood, and Bayesian) and also established the time divergenceof the phylogeny. The phylogeny successfully separated the primates into their taxonomic groupsas well as by their dietary preferences. Of note, the reviewed time of divergence estimation for theprimate speciation pattern in this study was more recent than the previously published estimates. It isbelieved that this difference may be due to environmental changes, such as food scarcity and climate change, during the late Miocene epoch, which forced primates to change their dietary preferences.These findings provide a starting point for further investigation.